RNA diagnostics and therapeutics: a comprehensive review - Adeela Fathima Saju; Aditi Mukundan; Divyashree MS; Raghu Chandrashekhar; Archana Mahadev Rao (RNA Biology)
RNA-focused therapy and diagnostics have been making waves in molecular biology due to the advantages RNA has over DNA; for instance, the ability of RNA to target nearly any genetic component in the cell is a big step in treating disorders. Moreover, RNA-based diagnosis of diseases is only becoming increasingly popular, especially after the COVID-19 pandemic, which brought up the need for cost-effective and efficient diagnosing kits for the vast majority. RNA-based techniques also have close to no risk of genotoxicity and can efficiently target undruggable regions of the cell. RNA treatments have effectively shown the future of the medical industry in the past couple of decades, and they will only be seen to improve. This review paper provides an overview on the different techniques that use RNA-based approaches in the field of diagnostics and therapeutics.